Five Trends Shaping Retail from 2020-2025 - Kumar, Rishi (Eximia, 2021)
Predicting the future of retail is tricky business. Who could have predicted what happened to retail in 2020? But the events of 2020 in some ways accelerated some trends that were happening already. Here are five trends shaping how retail evolves over the next five years.